Clinical outcomes and mortality risk of in-hospital cardiac arrest in patients with acute myocardial infarction complicated by cardiogenic shock - Zhang, Jing; Shao, Chengcheng; Zhu, Jiajia; Li, Jiang; Chen, Liying (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThis study investigated the clinical characteristics of in-hospital cardiac arrest (IHCA) in patients with acute myocardial infarction (AMI) complicated by cardiogenic shock and assessed the related in-hospital and post-discharge mortality.MethodsThis study included 148 patients with AMI complicated by cardiogenic shock who were admitted to the Cardiac Critical Care Center, Department of Cardiology, Beijing Anzhen Hospital, Capital Medical University between September 1, 2021 and July 31, 2024. Study participants were divided into two groups according to the occurrence of IHCA (IHCA group, n = 62 and control group, n = 86). The primary endpoint was in-hospital mortality, whereas secondary endpoints included in-hospital complications (e.g., ischemic stroke, hemorrhagic stroke, gastrointestinal bleeding, and lower limb ischemia), 30-day post-discharge mortality, and 1-year post-discharge mortality. The association between IHCA and in-hospital mortality was assessed by Cox regression analysis, and post-discharge mortality risks were evaluated by modified Poisson regression analysis.ResultsIHCA was associated with significantly higher in-hospital mortality (61.3% vs. 29.8%, P < 0.001), 30-day mortality (67.7% vs. 39.3%, P = 0.001), and 1-year mortality (71.0% vs. 40.5%, P = 0.001) compared with the control group. Cox regression analysis showed that IHCA increased the risk of in-hospital mortality [hazard ratio [HR] 2.064, 95% confidence interval [CI] 1.180–3.609, P = 0.011]. The relative risks of death within 30 days and 1 year post-discharge were 1.606 (95% CI 1.172–2.201, P = 0.003) and 1.644 (95% CI 1.216–2.222, P = 0.001), respectively. IHCA patients with non-reversible cardiac arrest had a higher 30-day mortality risk [relative risk (RR) 1.599, 95% CI 1.118–2.286, P = 0.010] than those with reversible cardiac arrest, although no significant difference was observed in the risk of 1-year mortality (RR 1.369, 95% CI 0.975–1.922, P = 0.070).ConclusionsIHCA increases in-hospital, 30-day, and 1-year mortality risks in patients with AMI complicated by cardiogenic shock. Non-reversible cardiac arrest notably increases the risk of death within 30 days post-discharge.